1985
DOI: 10.1002/med.2610050203
|View full text |Cite
|
Sign up to set email alerts
|

The use of microorganisms for the study of drug metabolism

Abstract: The potential for the use of microorganisms as tools in the study of drug metabolism appears to be unlimited. The selected examples cited here are only the beginning of what could develop into a widely accepted alternative in vitro model system for studying drug metabolism in humans. As with any other in vitro model system, it is not expected that microbial systems could ever replace animals in biomedical research. The acquisition of data regarding absorption, distribution, and excretion will still require who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 66 publications
0
48
0
Order By: Relevance
“…The IR spectra were recorded on a ATI Mattson Genesis Series FTIR spectrophotometer. The 1 H-and 13 C-NMR spectra were recorded in DMSO-d 6 on a Bruker AMX-500 spectrometer operating at 500 MHz for 1 H-and at 125 MHz for 13 C-NMR. The HRMS spectra were measured on a Bioapex FT-ICR MS with electrospray ionization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectra were recorded on a ATI Mattson Genesis Series FTIR spectrophotometer. The 1 H-and 13 C-NMR spectra were recorded in DMSO-d 6 on a Bruker AMX-500 spectrometer operating at 500 MHz for 1 H-and at 125 MHz for 13 C-NMR. The HRMS spectra were measured on a Bioapex FT-ICR MS with electrospray ionization.…”
Section: Methodsmentioning
confidence: 99%
“…11,12) Metabolism studies have been used successfully as model systems to predict metabolic pathways in humans or to increase the efficacy of drugs by metabolic activation. 13) Steroidal alkaloids have been investigated in metabolism studies due to their interesting biological activities.…”
mentioning
confidence: 99%
“…Traditionally, drug metabolism studies were conducted on small animal models, perfused organs, tissue culture, microsomal preparation [5,6] in vitro enzyme systems and in vitro cell cultures. Microbial model was developed as one of the in vitro model to overcome the disadvantages of other models.…”
Section: Introductionmentioning
confidence: 99%
“…The use of microbial systems for the in vitro investigation of drug metabolism has been extensively reviewed (Smith and Rosazza 1983 ;Clark et al 1985) since it was first demonstrated that micro-organisms were capable of a wide range of metabolic biotransformations which closely parallel mammalian phase I metabolism (Smith and Rosazza 1975). The use of micro-organisms overcomes many of the difficulties associated with using mammalian systems in vivo and in vitro (Clark et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The use of micro-organisms overcomes many of the difficulties associated with using mammalian systems in vivo and in vitro (Clark et al 1985). The isolation of a fungus, Verticillium lecanii, which is capable of mediating the chiral inversion of the non-steroidal anti-inflammatory drug, ibuprofen, and 2-phenylpropionic acid (2-PPA), a model substrate (Hutt et al 1993 ;Hanlon et al 1994) has previously been reported.…”
Section: Introductionmentioning
confidence: 99%